2020
DOI: 10.1002/qj.3806
|View full text |Cite
|
Sign up to set email alerts
|

Recalibrating wind‐speed forecasts using regime‐dependent ensemble model output statistics

Abstract: Raw output from deterministic numerical weather prediction models is typically subject to systematic biases. Although ensemble forecasts provide invaluable information regarding the uncertainty in a prediction, they themselves often misrepresent the weather that occurs. Given their widespread use, the need for high‐quality wind‐speed forecasts is well‐documented. Several statistical approaches have therefore been proposed to recalibrate ensembles of wind‐speed forecasts, including a heteroscedastic truncated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
(85 reference statements)
2
19
0
Order By: Relevance
“…This work investigates how weather types can be used to calibrate ensembles of weather forecasts, focusing in particular on how such approaches can be applied in an operational setting. A mixture model approach to include regime information into statistical post-processing methods has previously been proposed (Allen et al, 2019(Allen et al, , 2020, though these studies have utilised large sets of data, which are not always readily available to forecasting centres. To circumvent this lack of data, this work combines a conventional ensemble model output statistics approach with a regime-dependent method, producing a prediction system that can adapt to issue the most relevant forecast given the current circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This work investigates how weather types can be used to calibrate ensembles of weather forecasts, focusing in particular on how such approaches can be applied in an operational setting. A mixture model approach to include regime information into statistical post-processing methods has previously been proposed (Allen et al, 2019(Allen et al, , 2020, though these studies have utilised large sets of data, which are not always readily available to forecasting centres. To circumvent this lack of data, this work combines a conventional ensemble model output statistics approach with a regime-dependent method, producing a prediction system that can adapt to issue the most relevant forecast given the current circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the weights in this case are functions of time, rather than parameters as such, highlighting that the weights will change depending on the prevailing behaviour of the atmosphere. Potential approaches to calculate the mixture model weights are discussed in Allen et al (2020), where it is found that, in comparison with alternative choices, the regimes predicted by high-resolution numerical weather models provide a reasonable estimate of the future synoptic-scale state. As well as recording the regime that manifests, the Met Office store the daily regime that is forecast by their global deterministic model, up to 6 days in advance.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations